Genetic diversity in Egeria densa and E. najas in Jupia Reservoir, Brazil - Mori, Edson Seizo [UNESP]; Martins, Dagoberto [UNESP]; Velini, Edivaldo Domingues [UNESP]; Marino, Celso L. [UNESP]; Gouvea, Cantidio F.; Leite, Suzi M. M. [UNESP]; Camacho, Edwin [UNESP]; Guries, Raymond P. (Pontificia Univ Catolica Chile, Fac Agronomia Ingenieria Forestal, 2012)
E.S. Mori, D. Martins, E.D. Velini, C.L. Marino, C.F. Gouvea, S.M.M. Leite, E. Camacho Palomino, and R.P. Curies. 2012. Genetic diversity in Egeria densa and E. najas in Jupia Reservoir, Brazil. Cien. Inv. Agr. 39(2):321-330. The aquatic plant species Egeria densa (Planch.) Casp and E. najas Planchon occur naturally in the Parana River Basin of southeastern Brazil. Hydroelectric dam construction in the river basin has created several lakes, changing the ecology of the river and altering the population ecology of Egeria. Large, dense populations of Egeria now grow in Jupia Lake and its tributaries, occasionally blocking hydroelectric turbines. This study is part of a larger project examining environmental changes associated with large dam projects; the research objective of this study was to assess patterns of genetic diversity in Egeria populations growing in Jupia and Tres Irmaos Lakes and their Parana River tributaries using genetic markers. Forty-two plants of E. najas and 46 of E. densa (for a total of 88 samples) were collected from 13 sites. Genotypes were identified by isoenzymes and Random Amplification of Polymorphic DNA RAPD markers. Using a genetic distance dendrogram we grouped all E. densa plants into one set and all E. najas plants into another set. The plant sample 8a, which presented intermediary morphological characteristics of both species, also presented intermediary genetic characteristics, indicating the possibility that gene introgression between these Egeria species may occur. The creation of Tres Irmaos Lake appears to have increased some measures of genetic diversity in Egeria populations by facilitating outcrossing among previously semi-isolated genotypes. Increased migration of large numbers of seeds and vegetative branches of E. densa and E. najas into Jupia Lake and its tributaries can account for most of the changes in patterning of genetic diversity observed in these populations of Egeria.

Las especies acuáticas de Egeria densa y E. najas ocurren naturalmente en la Cuenca del Río Paraná, sudeste del Brasil. La construcción de una represa hidroeléctrica en la cuenca de este río, creó varios lagos, cambiando la ecología del río y alterando la populación ecológica de Egeria. Grandes y densas poblaciones de Egeria crecen hoy en día en el lago de Jupiá y sus afluentes, bloqueando de vez en cuando las turbinas de la hidroeléctrica. Como parte de un estudio de cambios ambientales, asociados a grandes proyectos de represas, fueron usados marcadores moleculares para determinar patrones de diversidad genética en las poblaciones de Egeria que crecen en los lagos de Jupiá, Três Irmãos y sus afluentes del Río Paraná. En un total de 13 sitios, fueran colectadas 42 plantas de E. najas y 46 de E. densa, que suman un total de 88 muestras. Los genotipos fueron identificados por marcadores de isoenzimas y RAPD. A través de dendrogramas de distancia genética se agruparon por separado todas las plantas de E. densa y de E. najas. La muestra 8a presentó plantas con características morfológicas e genéticas intermediarias de ambas las especies, indicando haber posibilidades de introgresión de genes entre ambas las especies de Egeria. La creación del lago de Três Irmãos parece haber aumentado, en alguna medida, la diversidad genética de las populaciones de Egeria por la facilidad de cruzamientos entre genotipos, hasta entonces semi-aislados. La migración creciente de grandes cantidades de semillas y de partes vegetativas de Egeria densa y Egeria najas dentro del Lago Jupiá y sus afluentes, pueden explicar los cambios observados en los patrones de diversidad genética en estas populaciones de Egeria.
Diversidad genética en plantas acuáticas de Egeria densa y E. najas en el lago de Jupiá
Keywords: Egeria; dam; isoenzyme; genetic distance; RAPD; reservoir